Craniectomy and Traumatic Brain Injury in Children on Extracorporeal Membrane Oxygenation Support. Issue 11 (November 2018) - Anton-Martin, Pilar; Braga, Bruno; Megison, Stephen; Journeycake, Janna; Moreland, Jessica
Abstract : Abstract: Severe trauma may cause refractory life-threatening respiratory failure requiring extracorporeal membrane oxygenation (ECMO). Concurrent traumatic brain injury, however, complicates the use of ECMO because of the major risk of intracranial bleeding with systemic anticoagulation. Craniotomy and/or craniectomy for hematoma evacuation during ECMO are extremely high-risk procedures secondary to ongoing anticoagulation, and there are only a few such case reports in the literature. We present the case of a child with multiple thoracic injuries and life-threatening respiratory failure supported on ECMO. She developed an intracranial hemorrhage while systemically heparinized that required emergent decannulation and bedside craniectomy for hematoma extraction. She survived with an excellent neurologic outcome. We also review the relevant literature regarding the use of ECMO in patients with polytrauma and the occurrence of craniectomy on extracorporeal support, with a focus on pediatric publications. Patients with polytrauma with brain injury can be supported on ECMO, but extreme precaution must be taken regarding anticoagulation. The intracranial complications of ECMO in this population are not infrequent, but our case report and review of the literature suggest that neurosurgical intervention should be considered in life-threatening conditions when no other alternatives are available.